PTP Inhibitor XIX Inhibits DUSP22 by Conformational Change. (9th January 2019) - Le, Hien Thi Thu; Cho, Young‐Chang; Lee, Sewoong; Kim, Yang‐Gyun; Kim, Kwonseop; Park, Sung Goo; Park, Byoung Chul; Cho, Sayeon
Abstract : Protein tyrosine phosphatases (PTPs) play critical roles in signal transduction by dephosphorylating regulatory proteins involved in many signaling cascades. PTP inhibitors have been reported as potential drugs to treat diseases induced by PTP activity. In this study, we show that PTP inhibitor XIX (PI‐19) inhibits dual‐specificity phosphatase 22 (DUSP22). Kinetic analysis of PI‐19 and DUSP22 suggests that PI‐19 inhibits DUSP22 at the catalytic site. In addition, we performed drug affinity responsive targets stability (DARTS) analysis to reveal that the conformation of DUSP22 changed upon binding to PI‐19. Moreover, PI‐19 blocked DUSP22‐mediated dephosphorylation of the signal transducer and activator of transcription 3 (STAT3) at Tyr‐705, a critical site for STAT3 activity. Collectively, our results imply that PI‐19 is an effective inhibitor of DUSP22 that regulates STAT3 activity. Abstract :